Paroxetine blunts the corticosterone response to swim-induced stress and increases depressive-like behavior in a rat model of postpartum depression. (March 2018) - Overgaard, Agnete; Lieblich, Stephanie E.; Richardson, Robin; Galea, Liisa A.M.; Frokjaer, Vibe G.
Highlights: Postpartum corticosterone for 14 days tended to induce depressive-like behavior in rats. Paroxetine increased depressive-like behavior by mid postpartum. Paroxetine blunted stress-induced corticosterone response early and mid postpartum. Abstract: Perinatal depression (PND) affects 15% of women. During the perinatal period both stress- and gonadal hormones fluctuate widely. Putatively, these fluctuations are involved in PND disease mechanisms. The serotonin system is sensitive to such hormone fluctuations, and serotonin reuptake inhibitors (SSRIs) are used to treat PND, although treatment is suboptimal and it is not known at which peripartum time-point SSRI treatment may be most efficacious. In this study, we investigate the effect of the SSRI paroxetine (5 mg/kg s.c.) on swim stress-induced corticosterone in a rat model of postpartum depression. In the rat model corticosterone (CORT; 40 mg/kg s.c.) was administered in Sprague Dawley rats across postpartum day (PD)2 to PD14. Stress response was measured during the first exposure to the forced swim test (FST1), and depressive-like behavior was measured in both FST1 and FST2. We found that paroxetine completely blunted the swim stress-induced CORT response and increased depressive-like behavior in both FST1 and FST2. Our findings suggest that in the postpartum context, SSRIs compromise stress axis dynamics, which are needed for a healthy stress response. This is likely unfavorable for reversing depressive-like behavior and may provide a rationale for augmentation strategies beyond SSRIs alone to optimize the clinical management of PND.